Integrasi Sistem Kendali Lengan Robot pada Preparasi Mikrokapsul Brachytherapy - El Wahyu, Jasmine; Abimanyu, Adi; Wijaya, Rio Natanael (Jurnal Otomasi Kontrol dan Instrumentasi, 2023)
HDR brachytherapy uses Ir-192 wrapped in microcapsules (seeds). Ir-192 requires high precision during the preparation process to produce good-quality seeds. The technological innovation of four DoF robot arms using LabVIEW and Arduino MEGA is equipped with an endoscope camera monitoring system to maximize preparation and minimize radiation exposure. The endoscope camera helps identify and observe seeds picked up by the vacuum gripper. The system starts by taking the seeds on the conveyor and placing them at the chuck. The robotic arm's test for accuracy and precision employs quantitative analysis. The linear motion angle test results in precision of 99.3% and accuracy of 100%; the base had 98.4% precision and 98.4% accuracy; Link 1 had 96.2% precision and 97.2% accuracy; and Link 2 had 72.4% precision and 71.5% accuracy. The average error of the inverse kinematics test was obtained: linear motion 0%, base 8.1%, Link 1 8.2%, and Link 2 9.8%. The average error of forward kinematics testing for positions a and z 0%, position x 25.1%, and position  y 18.9%. The average success result for the seed collection test was 87%, the monitoring test result was 80%, and the seed placement test was 86%. The overall system test results yielded 80% for monitoring, picking, and placing seeds, with an average system accumulation time of 83.6 seconds.